Auditory performance of reproduced sound field in aircraft cabin mock-up by feedback controlled multichannel least-square equalization method. (1st March 2023) - Yu, Yong; Zheng, Xu; Liu, Lianyun; Qiu, Yi; Dai, Zheng; Cui, Yi
Abstract: The cost of experimental evaluation on the acoustic environment in an aircraft during the flight is enormous. Building a cabin mock-up on the ground and reproducing the acoustic environment based on the method of sound field reproduction is of great significance for subsequent noise reduction and sound quality research. In this paper, feedback control was combined with general multichannel least-square equalization method, and the target sound field recording from a real flight was reproduced in an aircraft cabin mock-up. The frequency error was controlled within 3 dB in all frequency bands. In addition, the reproduction errors of psychoacoustics parameters, such as loudness and sharpness, were obviously reduced, indicating that the auditory perception of reproduced sound field was in consistent with target sound. Highlights: The acoustic environment in an aircraft was reproduced in a mock-up using feedback controlled multichannel least-square equalization method. The proposed method can significantly reduce the sound pressure level errors without changing the Tikhonov regularization parameters. The psychoacoustic parameters of the reproduced sound field were analyzed systematically.